Psicologia e Fenomenologia: um estudo da angústia em May, Heidegger e Boss - Avelar, Isabella Ferreira Vilela (2024)
The anguish, even being an existential condition of human still seems not elaborated in the way it should. That happens because anguish isn’t understood or accepted in our contemporary world. The Covid-19 Pandemic that occurred in recent years presented new ways of social interaction such as restrictions and abrupt ruptures in social and family relationships, turning the anguish an explicit affect. This created a new challenge for psychologists who increasingly came across the experience of anguish within the clinic with their clients/patients. The psychologist, in this sense, appeared as the professional who can deal with anguish interventively, since it has been felt as a concrete psychological experience. It is common to all that the understanding of anguish seems to be based more on philosophical than psychological bases, especially in a phenomenological-existential view. Thus, identifying the relevance of this analysis, starting from philosophical conceptions to a properly psychological conception, this research aimed to understand the analytical path of anguish from phenomenological philosophy to Psychology and Psychotherapy. To reach such an understanding, we understand the importance of retracing the space of anguish throughout the historical and cultural development of human beings; explain the position of philosophical phenomenology, especially the hermeneutic phenomenology of M. Heidegger; direct the ontological-ontic passage promoted by the Daseinsanalysis of L. Binswanger and M. Boss; and, finally, expose and analyze how anguish was conceived by the American psychologist R. May.